Calcium dependence of inactivation of calcium release from the sarcoplasmic reticulum in skeletal muscle fibers (The Rockefeller University Press, 1991)
The steady-state calcium dependence of inactivation of calcium release from the sarcoplasmic reticulum was studied in voltage-clamped, cut segments of frog skeletal muscle fibers containing two calcium indicators, fura-2 and anti-pyrylazo III (AP III). Fura-2 fluorescence was used to monitor resting calcium and relatively small calcium transients during small depolarizations. AP III absorbance signals were used to monitor larger calcium transients during larger depolarizations. The rate of release (Rrel) of calcium from the sarcoplasmic reticulum was calculated from the calcium transients. The equilibrium calcium dependence of inactivation of calcium release was determined using 200-ms prepulses of various amplitudes to elevate [Ca2+] to various steady levels. Each prepulse was followed by a constant test pulse. The suppression of peak Rrel during the test pulse provided a measure of the extent of inactivation of release at the end of the prepulse. The [Ca2+] dependence of inactivation indicated that binding of more than one calcium ion was required to inactivate each release channel. Half-maximal inactivation was produced at a [Ca2+] of approximately 0.3 microM. Variation of the prepulse duration and amplitude showed that the suppression of peak release was consistent with calcium-dependent inactivation of calcium release but not with calcium depletion. The same calcium dependence of inactivation was obtained using different amplitude test pulses to determine the degree of inactivation. Prepulses that produced near maximal inactivation of release during the following test pulse produced no suppression of intramembrane charge movement during the test pulse, indicating that inactivation occurred at a step beyond the voltage sensor for calcium release. Three alternative set of properties that were assumed for the rapidly equilibrating calcium-binding sites intrinsic to the fibers gave somewhat different Rrel records, but gave very similar calcium dependence of inactivation. Thus, equilibrium inactivation of calcium release appears to be produced by rather modest increases in [Ca2+] above the resting level and in a steeply calcium-dependent manner. However, the inactivation develops relatively slowly even during marked elevation of [Ca2+], indicating that a calcium-independent transition appears to occur after the initial calcium-binding step.